Clinical outcome of out-of-hospital vs. in-hospital cardiac arrest survivors presenting with ventricular tachyarrhythmias - Müller, Julian; Behnes, Michael; Schupp, Tobias; Reiser, Linda; Taton, Gabriel; Reichelt, Thomas; Ellguth, Dominik; Borggrefe, Martin; Engelke, Niko; Kern-Bollow, Armin; Kim, Seung‑Hyun; Weidner, Kathrin; et al. (Heart and vessels, 2022)
Limited data regarding the prognostic impact of ventricular tachyarrhythmias related to out-of-hospital (OHCA) compared to in-hospital cardiac arrest (IHCA) is available. A large retrospective single-center observational registry with all patients admitted due to ventricular tachyarrhythmias was used including all consecutive patients with ventricular tachycardia (VT) and fibrillation (VF) on admission from 2002 to 2016. Survivors discharged after OHCA were compared to those after IHCA using multivariable Cox regression models and propensity-score matching for evaluation of the primary endpoint of long-term all-cause mortality at 2.5 years. Secondary endpoints were all-cause mortality at 6 months and cardiac rehospitalization at 2.5 years. From 2.422 consecutive patients with ventricular tachyarrhythmias, a total of 524 patients survived cardiac arrest and were discharged from hospital (OHCA 62%; IHCA 38%). In about 50% of all cases, acute myocardial infarction was the underlying disease leading to ventricular tachyarrhythmias with consecutive aborted cardiac arrest. Survivors of IHCA were associated with increased long-term all-cause mortality compared to OHCA even after multivariable adjustment (28% vs. 16%; log rank p = 0.001; HR 1.623; 95% CI 1.002-2.629; p = 0.049) and after propensity-score matching (28% vs. 19%; log rank p = 0.045). Rates of cardiac rehospitalization rates at 2.5 years were equally distributed between OHCA and IHCA survivors. In patients presenting with ventricular tachyarrhythmias, survivors of IHCA were associated with increased risk for all-cause mortality at 2.5 years compared to OHCA survivors.
Online veröffentlicht: 16. November 2021
Gesehen am 19.07.2023